Моральное оправдание и нормативная составляющая теневых практик (К постановке проблемы) - Попова, И. (Социология: теория, методы, маркетинг, 2004)
The article presents sociological analysis of shadow practices in the post-soviet space,in Ukraine particularly. The analysis focuses on moral excuses and normative components of shadow practices in the context of value-and-normative grounds of market activity. There are discussed aspects of the shadow practice institutionalization and their realization mechanisms.